Eine neue Species von Discoloma Er. (Coleoptera: Notiophygidae). - John, Hans (Contributions to Entomology = Beiträge zur Entomologie, 1952)
Nomenclatural Acts sancatarinae John, 1952 (Discoloma), spec. n.